DATA KOMUNIKASI SECARA REAL TIME MENGGUNAKAN LONG RANGE (LORA) BERBASIS INTERNET OF THINGS UNTUK PEMBUATAN WEATHER STATION - Arifah Ramadhani; Zulpikar Alaudin; Farhan Jihad Arridha; Angga Rusdinar; Azzam Zamhuri Fuadi (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Weather station is a system needed to monitor weather conditions in an area. The sensors installed are usually located far from the monitoring center and the recording is done in real time time. For that we need a communication system that functions to send data from the sensor points to the monitor system. Communication built on weather station, uses Lora data communication, and the data sent consists of data from various sensors. The sensors used in the weather station are; temperature, humidity, light intensity, air pressure, rainfall, wind direction, and wind speed. All sensor data will be sent from the node to the gateway to be forwarded to the server Internet of Things. Communication utilizes LoRa which is installed in 2 nodes and 1 gateway in topology star and half-duplex. In this system, distance testing is carried out on LoS and NLoS against RSSI, SNR, delay, throughput, and packets. loss. The data was successfully obtained at LoS as far as 1 km and NLoS 500 m. Data received by the gateway is successfully monitored on Thingspeak in real time.